Brauchen mehrsprachige Jugendliche eine andere fach- und sprachintegrierte Förderung als einsprachige? - Prediger, Susanne; Wessel, Lena (Zeitschrift für Erziehungswissenschaft)
Keywords: Education

Is Formal Language Proficiency in the Home Language Required to Profit from a Bilingual Teaching Intervention in Mathematics? A Mixed Methods Study on Fostering Multilingual Students’ Conceptual Understanding - Schüler-Meyer, Alexander; Prediger, Susanne; Kuzu, Taha; Wessel, Lena; Redder, Angelika (International Journal of Science and Mathematics Education)
Keywords: General Mathematics; Education

The crucial first year: a longitudinal study of students’ motivational development at a Swiss Business School - Brahm, Taiga; Jenert, Tobias; Wagner, Dietrich (Higher Education)
In Switzerland, every student graduating from grammar school can begin to study at a university. This leads to high dropout rates. Although students’ motivation is considered a strong predictor of performance, the development of motivation during students’ transition from high school to university has rarely been investigated. Additionally, little is known about the relation of motivational aspects with other influences on study performance. The present longitudinal study addresses this research gap and examines the development of economics and management students’ study motivation. It encompasses four waves of data collected throughout the first year, using quantitative online surveys. In total, the sample consists of 820 students. Data is analysed using latent change modelling. Results indicate that students start at a higher level of intrinsic motivation compared to extrinsic motivation. The variability of the starting value of the two constructs is also differing. The analysis also shows a gradual decline in students’ motivation. Above all, the transition from secondary to higher education seems to be a driver for this decline.
Keywords: Transition to higher education; Motivation; Longitudinal study; Socio-cultural factors; Latent change model; Switzerland

Suggestions for Vocabulary Focused Reading Lessons for Mainstream Classrooms Addressing Both L1 and L2 Learners - Seifert, Susanne; Kulmhofer, Andrea; Paleczek, Lisa; Schwab, Susanne; Gasteiger-Klicpera, Barbara (Early Childhood Education Journal)
Keywords: Developmental and Educational Psychology; Education

The self-fulfilling prophecy of fear of academic failure - Brahm, Taiga; Jenert, Tobias; Wagner, Dietrich
Academic success in Higher Education is influenced by a number of different factors. This paper tackles the question if the individual levels of motivation, anxiety, enjoyment and self-efficacy, measured immediately before entering university, influence the probability of academic success. Former studies have shown an influence of the high school grade, the learning environment and motivational variables. They do not investigate, however, the individual levels of the mentioned constructs before the beginning of the studies. This research was conducted at the University of St. Gallen/Switzerland. The sample includes 695 first-year students who provided information about the individual level of the mentioned constructs. Descriptive statistics show that on average the students are highly motivated, have a high level of self-efficacy and are looking forward to their studies before their beginning. Yet, there are students who have a high level of fear of failure in the study in spite of their high motivation and self-efficacy. A logistic regression shows that there is a significant effect of fear of failure on the probability of study success. This paper shows that fear of failure can increase the probability of academic failure and thus become a self-fulfilling prophecy. It confirms fear as an important factor for academic success. Furthermore, other important factors for academic success, for example the high school grade, could be confirmed in this study
Keywords: Quantitative methods; Student learning; Emotion and Cognition; Social sciences; Higher education; Motivation and Emotion; Fear of Failure

A person-centred approach to students' transition into Higher Education - Brahm, Taiga; Wagner, Dietrich; Jenert, Tobias
A highly selective first study phase in many Swiss study programs leads to a rather competitive climate among students. However, the atmosphere at the university is an important factor for students' transition into Higher Education. An important question in this context is whether students' are equipped with different dispositions influencing how they cope with this transition. Other research has already shown that different groups of students can be identified regarding their student behavior. Yet, so far little is known about patterns of variables characterizing students, transitioning successfully. The paper takes advantage of a person-centered approach, i.e. the latent-class analysis, which makes it possible to identify groups of individuals, sharing common attributes. The research was conducted as a longitudinal study during their first year at a Swiss university. The return rate was about 67%, with 820 utilizable questionnaires at t1. Based on the analysis of students' anxiety, intrinsic motivation and self-efficacy, three distinct classes of students could be identified. The first class can be called the "highly motivated and self-confident" students. The second class is characterized by the same pattern, however, on a more intermediate level and the last class can be described as the "least motivated and most anxious" group of students. This study contributes to research and theory on students' transition into higher education and could be a first hint that students' experiences of this transition can vary substantially.
Keywords: Quantitative methods; Self-efficacy; Higher education; Motivation and Emotion

Zwischen Individuum, Institution und Disziplin: Methodologische Überlegungen zur Erfassung von Lernkulturen an Hochschule - Jenert, Tobias; Reinmann, Gabi (Dokumentation der Jahrestagung der Sektion Erwachsenenbildung der DGfE)
Keywords: Methodologie; Lernforschung; hochschuldidaktische Forschung; Higher Education

Effects of a Whole-Class Reading Program Designed for Different Reading Levels and the Learning Needs of L1 and L2 Children - Seifert, Susanne; Schwab, Susanne; Gasteiger-Klicpera, Barbara (Reading & Writing Quarterly)
Keywords: Linguistics and Language; Education

Massification of Higher Education in Taiwan: Shifting Pressure from Admission to Employment - Chan, Sheng-Ju; Lin, Liang-Wen (Higher Education Policy)
Keywords: Sociology and Political Science; Education

On the assessment of attitudes towards studying—development and validation of a questionnaire - Brahm, Taiga; Jenert, Tobias (Learning and individual differences : journal of psychology and education)
This research aims to develop and validate an instrument for the assessment of attitudes towards two particular objects: the Higher Education Institution (HEI) and the process of studying. Investigating attitudes towards studying at a HEI in a comprehensive way addresses an important research gap. It connects students' perception of the institution with teaching and learning. To validate the Assessment of Students' Attitudes towards Studying (ASAtS) Questionnaire, data was gathered at three different universities in Switzerland (820 students), Sweden (167) and Germany (133). Overall, the results show the internal consistency of the ASAtS. Its nomological validity is also supported by correlations with other constructs, such as intrinsic motivation and study performance. The ASAtS contributes to the theory on students learning by broadening the scope of research beyond learning in a narrow sense. From a practical point of view, it provides a tool for HE management to monitor students' perception of their HEI.
Keywords: Attitude; Student learning; Higher Education Institution; university; student experience